A comparison of C-MAC videolaryngoscope and Macintosh laryngoscope in intraocular pressure changes, throat pain, intubation time and hemodynamic variables - Özhan Çaparlar, Ceyda; Bumin Aydın, Gözde; Sezer, Evginar; Ergil, Jülide; Şanal Doğan, Aysun (The European Research Journal, 2019)
Objectives: The aim of the current study was to compare intraocular pressure (IOP), hemodynamic parameters and throat pain in the use of C-MAC videolaryngoscope and the Macintosh laryngoscope under general anesthesia requiring endotracheal intubation. Methods: Seventy-eight patients aged 18-65 years, ASA (American Society of Anesthesiologists physical status). I-II, who underwent elective surgery under general anesthesia were scheduled in the study. The groups were allocated as Group M (Macintosh laryngoscope) and Group VL (videolaryngoscope). Standard anesthesia technique was used in both groups. To assess the depth of anesthesia which was kept between 40 and 60, a Bispectral Index Monitor Model 2000 (Aspect Medical Systems, Inc, Newton, MA) was used throughout the study. We recorded hemodynamic variables, oxygen saturation before induction, at the 3rd and at the 10th minutes after intubation. The duration of intubation was recorded as the time from the laryngoscope entering the mouth to removal with end-tidal carbon dioxide on the monitor. IOP was measured before induction, and at the 3rd and 10th minutes after intubation. Inhalation agent was given after intubation. 78 patients were included in the study. We recorded cough after extubation, and postoperative sore throat was evaluated by an anesthesiologist who was blinded to the group allocations at 10 minutes and at 24 hours postoperatively. Results: There was no significant difference between the groups regarding age (p > 0.05), mean body mass index (p = 0.157), mean ASA (p = 0.475), mean bispectral index values (p = 0.084) and mean operating time (p = 0.068). The mean duration of intubation was determined to be statistically significantly longer in Group M than in Group VL (p = 0.0001). There was no statistically significant difference between the groups regarding Modified Mallampati Score (p = 0.571) and Cormack Lehane Score (p = 0.819). The mean IOP at 3rd minute after intubation was determined to be statistically significantly higher in Group M (p = 0.0001). There was no statistically significant difference between the groups in regarding cough after extubation (p = 0.549), throat pain at 10 minutes (p = 0.662) and at 24 hours postoperatively. Conclusions: C-MAC videolaryngoscope can be recommended as the first choice in patients with high IOP requiring general anesthesia with endotracheal intubation.